Determinants of Grade 9 Students’ Academic Performance in English - Roselyn M. Calixtro (Universitas Pendidikan Indonesia (UPI), 2022)
Academic performance in English is essential for every graduate to respond to the needs of global trends. Thus, every school is being challenged to produce globally competitive individuals. This study determined the relationship between students’ academic performance in English and; language literacy, study habits, parental support, and teachers’ teaching ability of Grade 9 students of Sto. Tomas College-Danao City, Cebu. The study utilized Descriptive Correlational Design and Pearson Product Moment Correlation Coefficient. The standardized tests were used in conducting the survey. The result revealed that academic performance was highly affected by study habits. Study habits had a great impact on the success of students’ academic performance in English. Among all the variables of the study, the students’ study habits got the lowest percentage mean score. This implied that though how well the students were being supported by the parents, how good were they in language literacy, and how good their teachers’ performance in teaching but they lack study habits still; it would lead to low academic performance. However, the other predictors still contributed to students’ performance with the support of good study habits. Therefore; it needs an intervention on how to improve the students’ study habits to develop good academic performance in English. Administrators, teachers, and parents should work hand in hand for students’ study habits enhancement and good academic performance.